Dangdut Koplo: Tubuh, Seksualitas, dan Arena Kekuasaan Perempuan - Maulana, Moh. Faiz (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2020)
This paper discusses the body, sexuality, and power relations of women through dangdut koplo music. Dangdut music is actually a Malay crystallization of orchestra that occurs because the people have such a close relationship with the people that represents their aspirations and desires. Therefore, dangdut is in great demand and loved by people in Indonesia. Dangdut identities with a singer; women and gesture (goyangan), make dangdut an attractive arena in the battle about the body, sexuality, and power relations over the body that are owned by singers. A singer can still show the independence of her body instead of being a commodity object. She can make her body the subject. There she is, she alone has the power to control her own body. This can be seen from the saweran incident, which was the relationship between the singer and the audience on the stage who had high bargaining and negotiating methods towards his body.